Exploring graphene oxide intrinsic electroactivity to elucidate the non-covalent interactions with DNA oligonucleotides - Liang, Yaquan (2022)
We show here how the electrochemical reduction signal of graphene oxide nanocolloids is inhibited upon the formation of non-covalent interactions with single stranded DNA oligonucleotides. The drop in the reduction current intensity is strongly influenced by the nucleobase sequence, and can therefore be directly correlated to the specific DNA homo-oligonucleotide.